Interactive Multimedia Development in Social Sciences Subject of Disaster Material at Grade IV SDN. (Public Elementary School) No.024183 East Binjai on 2017/2018 - Suwarti Suwarti; Restu Restu; Hidayat Hidayat (BIRCU, 2019)
This research deals with Interactive Multimedia Development in Social Sciences Subject of Disaster material in Grade IV SDN.(Public Elementary School) no. 024183 East Binjai on 2017/2018. As a product, interactive media is the result of solving a problem based on an audio-visual communication approach. The design of an interactive multimedia-based learning media is a visual communication design that is displayed through a monitor that can be presented at a certain time. The unavailability of learning media and the relevant learning models to be used because learning is not optimal, so the main focus of this research is the development of interactive multimedia-based learning media as an alternative in overcoming the problem of learning outcomes. This research was conducted from August 21 to November 20, 2017 in even semester at SDN (Public Elementary School) No. 024183 East Binjai having his address at Danau Laut Tawar Street, Sumber Mulyo Rejo, Binjai City, North Sumatra Province. Feasibility of using interactive multimedia on social studies subjects Disaster materials based on the results of validation from material experts and instructional media experts show that the average overall is categorized as